Peripheral monocyte functions and activation in patients with quiescent Crohn's disease. - David Schwarzmaier (Public Library of Science (PLoS), 2013)
Recent developments suggest a causal link between inflammation and impaired bacterial clearance in Crohn's disease (CD) due to alterations of intestinal macrophages. Studies suggest that excessive inflammation is the consequence of an underlying immunodeficiency rather than the primary cause of CD pathogenesis. We characterized phenotypic and functional features of peripheral blood monocytes of patients with quiescent CD (n = 18) and healthy controls (n = 19) by analyses of cell surface molecule expression, cell adherence, migration, chemotaxis, phagocytosis, oxidative burst, and cytokine expression and secretion with or without lipopolysaccharide (LPS) priming. Peripheral blood monocytes of patients with inactive CD showed normal expression of cell surface molecules (CD14, CD16, CD116), adherence to plastic surfaces, spontaneous migration, chemotaxis towards LTB4, phagocytosis of E. coli, and production of reactive oxygen species. Interestingly, peripheral blood monocytes of CD patients secreted higher levels of IL1β (p<.05). Upon LPS priming we found a decreased release of IL10 (p<.05) and higher levels of CCL2 (p<.001) and CCL5 (p<.05). The expression and release of TNFα, IFNγ, IL4, IL6, IL8, IL13, IL17, CXCL9, and CXCL10 were not altered compared to healthy controls. Based on our phenotypic and functional studies, peripheral blood monocytes from CD patients in clinical remission were not impaired compared to healthy controls. Our results highlight that defective innate immune mechanisms in CD seems to play a role in the (inflamed) intestinal mucosa rather than in peripheral blood.